Curriculum Development in Higher Education - Lakhe, Gajal (Nepal Journal of Medical Sciences, 2025)
Curriculum is one of the most frequently used terminology in the context of education. It is a vital part of education. It can be conceptualized as a well-organized plan for conducting educational activities in a school, college, university or in a specific course or program which helps the students learn effectively and efficiently. The process of curriculum development incorporates four major processes: need assessment, planning and design, implementation and evaluation. Curriculum implementation is the phase of putting the prescribed curriculum in action in the classrooms. The availability of adequate and trained human and material resources are the essence for the successful implementation of curricula. As curriculum is an ever-changing and ever-evolving process it needs to be evaluated time and again to ensure it meets academic standards, societal needs, and evolving educational trends. Even though teachers are the major implementers of curriculum however most of the teachers are not familiar with the process of curriculum development. The aim of this editorial is to clarify the concept of curriculum, to understand various strategies that has to be considered while designing a curriculum, steps involved in curriculum implementation and importance of curriculum evaluation.